1997
DOI: 10.1161/01.hyp.30.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Reduction of High Blood Pressure With Human Nitric Oxide Synthase Gene Delivery

Abstract: Endothelium-derived nitric oxide (NO) in peripheral vessels has been shown to modulate vascular resistance and blood pressure. We explored the effect of a continuous supply of human endothelial NO synthase (eNOS) on the blood pressure of spontaneously hypertensive rats (SHR) by somatic gene delivery. A DNA construct containing the human eNOS gene fused to the cytomegalovirus promoter/enhancer was injected into SHR through the tail vein. A single injection of the naked eNOS plasmid DNA caused a significant redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 38 publications
1
50
0
1
Order By: Relevance
“…30,39 Furthermore, in vivo gene transfer of eNOS to spontaneously hypertensive rats has resulted in direct blood pressure reduction. 40 Consistent with these studies, our data showed that gene transfer of eNOS significantly decreased O 2 Ϫ levels in carotid arteries in DOCA-salt rats. Taken together, these experimental observations support the novel concept that NO generated by recombinant NOS, as a result of vascular gene transfer, provides an effective means of inactivating O 2 Ϫ and thereby improving vasomotor function.…”
Section: Discussionsupporting
confidence: 89%
“…30,39 Furthermore, in vivo gene transfer of eNOS to spontaneously hypertensive rats has resulted in direct blood pressure reduction. 40 Consistent with these studies, our data showed that gene transfer of eNOS significantly decreased O 2 Ϫ levels in carotid arteries in DOCA-salt rats. Taken together, these experimental observations support the novel concept that NO generated by recombinant NOS, as a result of vascular gene transfer, provides an effective means of inactivating O 2 Ϫ and thereby improving vasomotor function.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, more attention has been paid to gene therapy for hypertension, which would produce a long-lasting effect without taking pills daily. The tested genes include those coding for atrial natriuretic peptide (Lin et al, 1997a), endothelial nitric oxide synthase (Lin et al, 1997b) and hKLK1 (Wang et al, 1995), among which hKLK1 gene has been proved to be more potential to achieve hypotensive effect. Here we present additional evidence that both hKLK1 gene delivery and rK1 administration can be used as alternative strategies for treating human hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, eNOS gene transfer may be an effective means in combating superoxide-induced vascular dysfunction and atherogenesis in hypertension. Moreover, a study in spontaneously hypertensive rats (SHR) has reported that a single injection of the naked eNOS plasmid DNA through the tail vein caused a significant reduction of blood pressure for 6 weeks, and a second injection maintained the effect up to 12 weeks (66). In this study, increased NO production was determined as increased urinary and serum nitrite /nitrate content as well as increased cGMP levels in the urine and aorta.…”
Section: -6 Hypertensionmentioning
confidence: 79%